THE EFFECT OF MICROCRYSTALLINE CELLULOSE ON THE MICROFLORA OF THE COLON - Koval, D. B.; Malyarchuk, H. R.; Levenets, O. O. (International Journal of Medicine and Medical Research, 2022)
Background. Nowadays, much attention is paid to enterosorption methods that allow cleansing the internal organs and removing extraneous substances out of the body of a sick person. Objective. The aim of the research was to study the effect of microcrystalline cellulose on the microflora of the large intestine. Methods. The study was performed on 50 white laboratory Wistar rats weighing 180-270 g, which were divided into control and experimental groups. The experimental group was daily administered with microcrystalline cellulose at a dose of 500 mg/kg. The study followed ethical standards and recommendations for the humanization of work with laboratory animals according to the “European Convention for the protection of vertebrate animals used for experimental and other purposes” (Strasbourg, 1986, 2010), as well as the requirements of the Commission on Bioethics of I. Horbachevsky Ternopil National Medical University (Minutes No. 66, dated November 01, 2021). The first group involved the intact rats on standard diet, the second – the rats, which received normal feeding of microcrystalline cellulose. Results. In the feces of the experimental white rats treated with microcrystalline cellulose, the level of Escherichia coli in the large intestine decreased by 22 and 25%. The number of these microorganisms increased by 20% in 7 days and by 14% in 14 days. The content of epidermal staphylococci in the stool decreased by 10% on the 7th day of administration. Microcrystalline cellulose increased the number of Staphylococcus aureus by 12%, but decreased the number of enterococci in the feces by 28%. In 7-14 days of the experiment, the content of these bacteria did not change significantly in the colon. In relation to anaerobic microorganisms – bacteroides and clostridia, this supplement caused a slight increase in the number of bacteroides – by 8.64% and the number of clostridia – by 11.54% on the 14th day. The content of fungi of the Candida genus on the 7th and 14th day increased by 8.3%. Conclusions. In the 2nd period of the study, the microbiome of intestinal contents worsened: the process of dysbacteriosis increased, which was manifested by a significant increase in the number of Proteus spp., Staphylococcus aureus, anaerobes (bacteroides, clostridia) and Candida spp., as well as decreased Escherichia coli and Enterococci.